2011
DOI: 10.1002/hipo.20808
|View full text |Cite
|
Sign up to set email alerts
|

Pattern separation deficits associated with increased hippocampal CA3 and dentate gyrus activity in nondemented older adults

Abstract: There is widespread evidence that memory deteriorates with aging, however the exact mechanisms that underlie these changes are not well understood. Given the growing size of the aging population, there is an imperative to study age-related neurocognitive changes in order to better parse healthy from pathological aging. Using a behavioral paradigm that taxes pattern separation (the ability to differentiate novel yet similar information from previously learned information and thus avoid interference), we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

82
526
3
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 499 publications
(615 citation statements)
references
References 69 publications
82
526
3
4
Order By: Relevance
“…Consistent with the predictions from the rodent work, both studies found that older adults tended to be biased more toward completion at the expense of separation. We also demonstrated that these behavioral impairments were correlated with hippocampal DG/CA3 network hyperactivity (20), consistent with the finding in the rodent that aged CA3 place cells exhibit generally elevated firing rates across novel and familiar environments (22).…”
supporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with the predictions from the rodent work, both studies found that older adults tended to be biased more toward completion at the expense of separation. We also demonstrated that these behavioral impairments were correlated with hippocampal DG/CA3 network hyperactivity (20), consistent with the finding in the rodent that aged CA3 place cells exhibit generally elevated firing rates across novel and familiar environments (22).…”
supporting
confidence: 90%
“…In this task, participants saw novel, repeated and similar lure items and were asked to indicate whether the item was "old," "similar," or "new." Our previous work (20) has shown that older adults have a diminished "separation bias" on this task compared with young adults (i.e., they were less likely to call lure items similar and more likely to call them old). We replicated this effect here (Fig.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations